Meningkatkan Keefektifan Pembelajaran Matematika Menggunakan Model Guided Discovery Learning pada Siswa IX-F SMPU Amanatul Ummah - Badrul Mutamam (Postulat : Jurnal Inovasi Pendidikan Matematika, 2021)
This research is a classroom action research which aims to describe the effectiveness of the mathematics learning model using the guided discovery learning model for class IX-F students of SMP Unggulan Amanatul Ummah Surabaya. This research was conducted in 4 stages, namely planning, acting, observating and reflecting. This study shows that learning using the guided discovery learning model can improve student learning outcomes, the ability of teachers to manage learning, and student activities during learning. Based on these three aspects, it can be concluded that learning using the guided discovery learning model can increase effectiveness in learning